STUDI KOMPARASI ACTIVITY-BASED-COSTING & TIME-DRIVEN-ACTIVITY-BASED-COSTING DALAM MENINGKATKAN KINERJA: SEBUAH TINJAUAN LITERATUR - Ulfatun Nikmah (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to classify differences in the characteristics of the impact of implementing ABC and TDABC in improving company performance. The method follows the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). The database search was done through science direct, emerald, cambridge, and sinta from 2017 to 2021. There are 93 articles, but after a screening test, only 20 articles were included. The results indicate that both ABC and TDABC can improve performance through the effectiveness and efficiency of cost production. However, both have different characteristics that must be considered in the implementation process. The implication of this study is to give insight to management for considering the use of ABC and TDABC.